The Innovation of English Learning Resources Utilizing Interactive Games Aimed at Elementary School Students in Desa Pasar X - Thereza Angie Grifin; Rani Amelia Sihite; Sabrina Wandani Hutabarat; Mesra Sinambela; Chairos Valentino Sibarani (Saniya Institute, 2024)
This study addresses the issue of insufficient utilization of effective learning media to enhance elementary school students' comprehension of the English language. The primary objective is to create interactive, game-based learning tools that facilitate a better understanding of English vocabulary among students. The research specifically targets elementary school students in Desa Pasar X Village, Kutalimbaru. Employing the Research and Development (R&D) methodology, the study follows the ADDIE model, which encompasses five phases: Analysis, Design, Development, Implementation, and Evaluation. Data collection methods included observation, as well as pre-test and post-test assessments to measure students' understanding. The implementation of interactive games, such as board games and plasticine activities, demonstrated significant effectiveness. The results from the post-test indicated a notable improvement in student comprehension, rising from 69.5% in the pre-test to 80.25%, thereby confirming that these media enhance students' retention and engagement in English learning. The successful development of interactive, game-based learning media has significantly bolstered students' grasp of English vocabulary, fostering a dynamic and enjoyable learning environment that encourages active participation and skill enhancement.